(untitled) (Medico Legal Update, 2020)
Ontology design and querying the data set to obtain accurate results has been a topic of research. The aim of the paper is to represent ontological knowledge in the field of Medical Information Systems to store the knowledge about Swine flu disease and thereby querying the data and formalize the knowledge base development. The developed knowledge from RDF is converted to rules and then querying is done through different methods and performance analysis has been done on the retrieved query. The results predicted determine the suitability of the method where querying gives the accurate result for swine flu disease ontology.